Graduate’s Personal and Professional Impact Assessment: A Degree Program Sustainability Criteria - Dolipas, Bretel; Lubrica, Maria Azucena; Oryan, Serano; Samuel , Freda Kate; Valentin, Precious; Lubrica, Joel; Buasen, Julie; Ocampo, Phil (Journal of Interdisciplinary Perspectives, 2025)
A degree program’s sustainability could be based on the impact of a completed degree on a graduate's personal and professional development. The study aimed to determine the sustainability of the Master of Arts in Applied Statistics MAAS Program of Benguet State University regarding how the degree responds to the graduates’ personal and professional developmental needs. The areas considered were knowledge-based development, skills development, attitude change, and task performance. All thirty-two- degree program graduates from 2001 to 2019 were the respondents of the study and a questionnaire was the main instrument used to gather data needed. Results showed that the extent of acquisition and utilization along the graduates’ knowledge development, skills development, attitude change, and task performance ranged from much acquired or utilized to very much acquired or used, with improved quality of output as the topmost competency acquired and utilized while "improved communication skills" as the least. The extent of contribution along the graduates’ knowledge development, skills development, attitude change, and task performance were considered many contributions, with improved quality of output as the topmost competency while improved communication skills as the lowest. The MAAS graduates considered earning the degree beneficial to their personal and professional development hence an important basis for the program’s sustainability. Teaching methods and strategies should be focused on giving more opportunities for MAAS students to express themselves orally and in writing.